Embracing Technology and Pop Culture Trends in Physical Education: Ready, Set, (Pokémon) Go!. Issue 4 (4th May 2018) - Bruno, Laura E.
Abstract : As physical education teachers, it is important to remain current with trends and continue to add fresh, innovative ideas to our lessons. This responsibility means that educators must continue to seek ways to better understand students and encourage a physically active lifestyle. This article provides strategies for embracing technology and the pop culture trend, Pokémon Go, in a geocaching physical education unit. Skeptics may argue that Pokémon Go does anything but promote fitness and physical activity, claiming that individuals walk aimlessly with their eyes glued to a screen. However, teachers can choose to approach this trend with opportunistic eyes and imaginative ideas. This article offers physical educators an application of the theory to practice framework, identifying how technology and pop culture trends can translate to the physical education classroom.